Electroacupuncture at PC6 (Neiguan) Improves Extracellular Signal-Regulated Kinase Signaling Pathways Through the Regulation of Neuroendocrine Cytokines in Myocardial Hypertrophic Rats. (24th August 2011) - Li, Jia; Li, Jing; Liang, Fengxia; Hong, Yaqun; Wu, Song; Tang, Hongtu; Wang, Hua
Abstract : Electroacupuncture (EA) therapy has been widely accepted as a useful therapeutic technique with low or no risk in the clinical prevention of cardiac hypertrophy. However, the signaling transduction mechanism underlying this effect remains unclear. The current study investigates the effects of EA on the signaling pathways of myocardial hypertrophy (MH) in rats. Up to 40 3-month-old Sprague-Dawley (SD) rats were randomly divided into normal, model, PC6 (Neiguan), and LI4 (Hegu) groups, with ten rats in each group. All the rats except for the normal group received 3 mg/kg⋅d of isoprinosine hydrochloride (ISO) injection into the back skin. The rats in the PC6 and LI4 groups received EA for 14 days. On the 15th day, electrocardiograms were recorded, and the ultrastructure of the myocardial cells was observed. The myocardial hypertrophy indices (MHIs), electrocardiograph (ECG), ultrastructure observation, levels of plasma angiotensin II (Ang II) and endothelin (ET), as well as protein expression of extracellular signal-regulated kinase (ERK), and phosphorylation extracellular signal regulating kinase (p-ERK) in the left ventricular myocardial tissue were measured. The results indicated that EA can improve cardiac function in MH rats by modulating upstream neuroendocrine cytokines that regulate the ERK signaling pathways.